SGLT1 Knockdown Attenuates Cardiac Fibroblast Activation in Diabetic Cardiac Fibrosis - Lin, Hui; Guan, Le; Meng, Liping; Uzui, Hiroyasu; Guo, Hangyuan (Frontiers in Pharmacology, 2021)
Background: Cardiac fibroblast (CF) activation is a hallmark feature of cardiac fibrosis in diabetic cardiomyopathy (DCM). Inhibition of the sodium-dependent glucose transporter 1 (SGLT1) attenuates cardiomyocyte apoptosis and delays the development of DCM. However, the role of SGLT1 in CF activation remains unclear. Methods: A rat model of DCM was established and treated with si‐SGLT1 to examine cardiac fibrosis. In addition, in vitro experiments were conducted to verify the regulatory role of SGLT1 in proliferation and collagen secretion in high-glucose– (HG–) treated CFs. Results: SGLT1 was found to be upregulated in diabetic cardiac tissues and HG-induced CFs. HG stimulation resulted in increased proliferation and migration, increased the expression of transforming growth factor-β1 and collagen I and collagen III, and increased phosphorylation of p38 mitogen-activated protein kinase and extracellular signal-regulated kinase (ERK) 1/2. These trends in HG-treated CFs were significantly reversed by si-SGLT1. Moreover, the overexpression of SGLT1 promoted CF proliferation and collagen synthesis and increased phosphorylation of p38 mitogen-activated protein kinase and ERK1/2. SGLT1 silencing significantly alleviated cardiac fibrosis, but had no effect on cardiac hypertrophy in diabetic hearts. Conclusion: These findings provide new information on the role of SGLT1 in CF activation, suggesting a novel therapeutic strategy for the treatment of DCM fibrosis.